Hubungan Gaya Kepemimpinan Kepala Sekolah, Budaya Organisasi dan Iklim Organisasi dengan Motivasi Berprestasi Guru - Prim Masrokan Mutohar (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
This study is aimed to describe the direct or indirect relationships between principals' leadership style, organizational culture, and organizational climate and teachers' achievement motivation. A survey design was applied in this study. The sample was consisted of 317 teachers taken from the population of 1354 teachers. Data were collected with a set of questionnaire and analyzed statistically using percentages and multiple regresion. The study revealed that there was significant relationship between the all variables in this study.